Pengaruh Work Life Balance dan Kepemimpinan Transformasional Terhadap Kinerja Karyawan Melalui Employee Engagement di RS Muhammadiyah Darul Istiqomah Kendal - Salsabila, Kinanti Faradita; Muchammad Rully Sjahirul Alim (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of work-life balance and transformational leadership on employee performance, mediated by employee engagement, among nurses and midwives at Muhammadiyah Darul Istiqomah Hospital, Kendal. Using a quantitative approach with 90 respondents and SmartPLS 4.0 for data analysis, results reveal that work-life balance significantly affects performance but not engagement. Conversely, transformational leadership positively influences engagement but not performance directly. These findings highlight that work-life balance supports performance quality, while transformational leadership through engagement can enhance employee productivity, underscoring the practical importance of balancing personal and professional life and adopting inspirational leadership styles in healthcare settings.